Role of Oxidative Stress in the Occurrence, Development, and Treatment of Breast Cancer - Rui Dong; Jing Wang; Ruiqi Guan; Jianwei Sun; Ping Jin; Junling Shen (Antioxidants)
Breast cancer is one of the most prevalent cancers worldwide. Recent studies have increasingly emphasized the role of oxidative stress in the initiation and progression of breast cancer. This article reviews how oxidative stress imbalance influences the occurrence and advancement of breast cancer, elucidating the intricate mechanisms through which reactive oxygen species (ROS) operate in this context and their potential therapeutic applications. By highlighting these critical insights, this review aims to enhance our understanding of oxidative stress as a potential target for innovative therapeutic strategies in the management of breast cancer.